Developing linkages for agricultural technology transfer: A case study of research institution and voluntary organization partnership - GAJBHIYE, RAHUL; NAIN, M S; SINGH, PREMLATA; CHAHAL, V P (The Indian Journal of Agricultural Sciences, 2015)
A paradigm shift to the private and voluntary organizations led extension is being witnessed as the public agricultural extension system has been adversely affected by various constraints. ICAR-Indian Agricultural Research Institute (IARI) a premier agricultural research institution took lead to develop linkages with voluntary organizations (VOs) of repute for speedy transfer of agricultural technologies to the ultimate users. The present study was conducted on randomly selected 120 farmers of Patiala district to analyze the effectiveness of IARI linkage with VO namely Young Farmers’ Association (YFA) of Punjab state. The advisory services through IARI-YFA linkage, higher yield of IARI released varieties, social participation of farmers and their education were the major determinants for the adoption of IARI varieties. In case of both rice and wheat, IARI varieties were sown in more than 60% area of the total land holdings of the farmers. Although, the linkage was perceived highly effective in terms of the delivery of farm technologies, advisory services, farm literature supplied, farmers’ fair, front line demonstrations, impact on yield and income of farmers and satisfaction of farmers but non-availability of seeds in desired quantity, higher seed cost and less land for seed multiplication were major inhibiting factors. The functional efficacy of linkage may be enhanced through close collaboration of state level government and private agencies for broad based, inclusive and sustainable agricultural development.